Carvedilol Attenuates Inflammatory Biomarkers and Oxidative Stress in a Rat Model of Ulcerative Colitis. Issue 4 (June 2015) - Fatani, Amal J.; Al‐Hosaini, Khaled A.; Ahmed, Mohammed M.; Abuohashish, Hatem M.; Parmar, Mihir Y.; Al‐Rejaie, Salim S.
ABSTRACT <table-wrap position="anchor" orientation="portrait"> Preclinical Research </table-wrap> This study evaluated the effects of the carvedilol, a nonselective β‐adrenoceptor anatgonist with α1‐adrenoceptor antagonist activity, in a rat model of experimentally induced ulcerative colitis (UC). UC was produced using acetic acid (AA) in animals previously treated with carvedilol (30 mg/kg po, qd) for seven days. Mucus content, lipid peroxidation (LPO) products, sulfhydryl groups, antioxidant enzyme activities, proinflammatory cytokines, prostaglandin E2 and nitric oxide levels were measured in colonic tissues and histopathological changes were assessed. LPO and proinflammatory biomarkers were markedly increased, while mucus content, sulfhydryl groups and enzymatic activities were inhibited in animals administered AA. Pretreatment with carvedilol attenuated LPO elevation, mucus content and sulfhydryl group inhibitions. Antioxidant enzymatic activity and proinflammatory biomarker levels were also restored in carvedilol‐pretreated animals. Colonic protection associated with carvedilol pretreatment was further confirmed by histopathological assessment and found to be similar to the standard therapy of mesalazine (100 mg/kg po qd), suggesting that the effects of carvedilol action may be attributable to its anti‐inflammatory and antioxidant properties. Drug Dev Res 76 : 204–214, 2015. © 2015 Wiley Periodicals, Inc.